Implementation of AI-based CTL learning model on students' mathematics learning outcomes - Yopi Ayomi Afandi; Noerhasmalina Noerhasmalina; Ana Istiani; Lisdwiana Kurniati; Korhan Cengiz (Hipotenusa Journal of Research Mathematics Education (HJRME), 2026)
This study was based on the low learning outcomes of students at SMP Negeri 4 Gadingrejo, where only 32 out of 126 students achieved the Learning Objective Achievement Criteria (KKTP). The research method used was quantitative with an experimental design, involving two groups: the experimental class (AI-based CTL) and the control class (Project Based Learning). The instrument used was a learning outcome test consisting of 5 essay questions that had been tested for validity and reliability. Data were analyzed to measure the differences in learning outcomes between the two groups. The results showed a significant difference between the average learning outcomes of students in the experimental class and those in the control class. The average learning outcomes of students who used the AI-based CTL model were higher than those who used the PjBL model. Based on the t-test, the calculated t value was 5.13, which was greater than the t-table value of 2.00, thus the research hypothesis was accepted. The conclusion of this study is that the application of the AI-based CTL learning model is effective in improving students’ learning outcomes on SPLDV material, and it is therefore recommended to consider using this model in mathematics learning.